Analisis kemampuan berpikir kritis pembagian pecahan pada mata pelajaran matematika peserta didik kelas v sekolah dasar - Theresia Vivi Lusiana; Slamet Slamet; Anesa Surya (Universitas Sebelas Maret, 2022)
The aim of this study was to describe critical thinking ability on the fraction division of fifth grade students at SD Negeri Tegalayu Surakarta. This study used qualitative research method, specifically qualitative case study. The subjects of this study were fifth grade students of SD Negeri Tegalayu, totalling 25 students. Data collection techniques in this study included interviews, observation, and documentation. The data validity technique in this study was triangulation that consisted of technical triangulation and source triangulation. The data were analysed by using interactive analytical model of Miles, Huberman, & Saldana. The results of this study showed that the ability to think critically was generally in the low category. The interpretation ability was in the medium category. The analytical ability was in the low category. The evaluation ability was in the low category. The inference ability was in the low category. The indicator of the lowest critical thinking ability was the inference indicator. Thus, this mathematical critical thinking study can be used as a reference for another study in other elementary schools. Besides school and teachers are expected to have the skills to develop students' critical thinking ability.